Effect of prophylactic noninvasive oxygen therapy after planned extubation on extubation failure in high-risk patients: a retrospective propensity score-matched cohort study - Zheng, Xiaozhuo; Lu, Lixiong; Ma, Mengyi; Lei, Xiaofeng (Frontiers in Medicine, 2024)
Background: Extubation failure (EF) is common in the intensive care unit (ICU) and is associated with poor prognosis, especially in high-risk patients. However, the efficacy of prophylactic noninvasive oxygen therapy (NIT), including noninvasive ventilation (NIV) and high-flow nasal cannula (HFNC), in reducing EF in high-risk patients remains controversial. Therefore, we aimed to evaluate the effect of post-extubation prophylactic NIT on EF in high-risk patients.This was a retrospective observational study conducted in the ICU from March 2018 to December 2023. We included adult patients at high risk for reintubation who were mechanically ventilated for over 24 hours and successfully passed the spontaneous breathing trial (SBT). Immediately after extubation, patients underwent NIT or conventional oxygenation therapy (COT). The primary outcome was the EF rate within 7 days after extubation.Results: There were 440 patients in the NIT group and 274 in the COT group. After propensity-score matching, 227 subjects were enrolled in each group. NIT reduced the rate of EF (18.0% vs 34.3%, p<0.001) and reintubation (10.5% vs 18.2% p=0.003) compared with COT, which was confirmed in propensity-matched cohort (17.6% vs 32.2%, p<0.001; 11.5% vs 19.8%, p=0.014). Multivariate logistic regression analysis indicated that prophylactic NIT (p=0.001) and higher ROX index (p=0.022) were associated with reduced risk of EF. While higher fluid balance (p=0.013), higher RSBI (p<0.001), and the occurrence of delirium (p=0.032) may be the risk factors for EF.Subgroup analysis showed that post-extubation NIT was more effective in elderly patients, and HFNC was noninferior to NIV in reducing EF. While HFNC had a tendency to reduce the incidence of delirium.Post-extubation prophylactic NIT is effective in reducing EF in high-risk patients, especially in the elderly patients. HFNC is an alternative treatment to NIV. Fluid balance, RSBI, ROX index, and delirium are associated with the occurrence of EF.